2006
DOI: 10.2337/diabetes.55.03.06.db05-1417
|View full text |Cite
|
Sign up to set email alerts
|

Increased Monocytic Activity and Biomarkers of Inflammation in Patients With Type 1 Diabetes

Abstract: , and monocyte function). High-sensitive CRP, soluble intracellular adhesion molecule (sICAM), sCD40L, and nitrotyrosine levels were significantly elevated in type 1 diabetic subjects compared with in control subjects (P < 0.05). Monocyte superoxide anion release was significantly increased in the resting (37%; P < 0.05) and activated state (26%; P < 0.005) in type 1 diabetic compared with in control subjects. Monocyte interleukin (IL)-6 levels were significantly elevated in type 1 diabetic subjects compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
192
1
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(219 citation statements)
references
References 45 publications
16
192
1
10
Order By: Relevance
“…Diabetes can be envisioned as a disease characterized by a chronic systemic inflammatory state disturbing the function of multiple vital body systems, in particular the vasculature (28,29). We hypothesized that hampered differentiation of EPC from myeloid progenitor cells in the BM might contribute significantly to the suboptimal endothelial repair under hyperglycemic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes can be envisioned as a disease characterized by a chronic systemic inflammatory state disturbing the function of multiple vital body systems, in particular the vasculature (28,29). We hypothesized that hampered differentiation of EPC from myeloid progenitor cells in the BM might contribute significantly to the suboptimal endothelial repair under hyperglycemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Given the proper differentiation factors, however, these BM precursor pools also give rise to important effector cells of the innate immune system such as macrophages (Mph) and dendritic cells (DC) (26,27), suggesting a common myeloid progenitor pool for EPC, Mph, granulocytes, monocytes, and DC. Because diabetes is increasingly being recognized to be a chronic systemic proinflammatory state (28,29), we hypothesized that the disturbed vascular repair in diabetes is related to an effect of hyperglycemia on the differentiation fate of myeloid BM precursors. We demonstrated that hyperglycemia indeed skews the BM potential from generating proangiogenic early EPC to the development of proinflammatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Proinflammatory cytokines TNF-α, IL-6, and MCP-1 produced from M1 adipose tissue-resident macrophages contribute to insulin resistance [241]. Ly-6C hi monocytes are predominant in the blood of type 1 diabetic animals [247], and the monocytes isolated from patients with diabetes secrete higher levels of proinflammatory cytokines [248][249][250]. It is believed that the cytokines released from these cells influence peripheral inflammatory status.…”
Section: Diabetesmentioning
confidence: 99%
“…However, metabolic disorders also appear to affect blood monocytes directly. A number of studies reported that monocytes both in patients with metabolic disorders and in dyslipidemic or diabetic mice undergo phenotypical and functional changes that may contribute directly to the development and progression of chronic inflammatory vascular diseases (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%